HealthStart : need for growth strategy - Jena, Sanjay Kumar; Laha, Arnab Kumar; Singh Ghura, Amarpreet K. (London : Indian Institute of Management, Ahmedabad, 2018)
The case describes the launch of Healthstart, a company that specialises in accelerating and investing in healthcare start-ups. Healthstart conducted annual accelerator programs around healthcare entrepreneurship and selected start up received 2.5 million INR for 10% equity. In 2017 the CEO of Healthstart, Pradeep Jaisingh, is considering how to develop a sustainable business model and to increase the number of start-ups that Healthstart can invest in per year.
Originally Published InJena, S. K., Laha, A. K., & Singh Ghura, A. K. (2018). HealthStart: Need for Growth Strategy. CMHS0041. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Healthstart -- Case studies; Medical economics -- Case studies; Health facilities -- Business management -- Case studies